In Vitro Fracture Strength of Teeth Restored with Lithium Disilicate Onlays with and without Fiber Post Build-Up - Nicola Mobilio; Alberto Fasiol; Francesco Mollica; Santo Catapano (MDPI AG, 2018)
To our knowledge there is no data about the mechanical performance of indirect restoration adhesively cemented on teeth without an adequate build-up to provide the correct geometrical configuration. The aim of this study was to compare the fracture strength of human teeth restored with lithium disilicate onlays, with and without fiber post build-up. Methods: Twenty human mandibular molars were horizontally sectioned and divided into two groups (n = 10). No treatment was applied in group A. Teeth in group B were endodontically treated, built-up using fiber post and composite core and prepared with a circumferential chamfer providing a 1 mm circumferential ferrule. Lithium disilicate onlays were pressed and luted on teeth using dual-curing luting composite. Teeth were tested under static load. Failures were classified as restorable or not restorable. Failure loads were analyzed with one-way analysis of variance. Failure modes were compared using Pearson’s Chi-square tests. Results: The mean fracture loads were 1383.5 N for group A and 1286.3 N for group B. No difference was found (p = 0.6). Ninety per cent of fractures were classified as not restorable in both groups, with no difference (p = 0.8). Conclusions: For teeth restored with adhesive procedures and lithium disilicate onlays, the presence of build-up with fiber post to provide retention and resistance form does not influence the fracture strength.